Hyperfractionated radiotherapy with concurrent chemotherapy in locally advanced head and neck cancer – An observational study - Dr. Namrata Bhagat; Dr. Vandana Jain; Dr. Chaitali Waghmare; Dr. Sanandan Patel (Medico Research Chronicles, 2019)
Introduction: Radiotherapy plays an important role in the multidisciplinary treatment of locally advanced head and neck cancer, but the rates of locoregional recurrence are high and survival is poor. Thus, there was an emergence of altered fractionation. The purpose of this study is to see the treatment overall response of Hyperfractionated Radiotherapy with concurrent chemotherapy in locally advanced Head and Neck Cancer patients.Material & Methods: This was an observational study conducted in the Department of Radiation Oncology, Pravara Rural Hospital, Loni between September 2018 to September 2019. Fifteen histopathologies proved patients with locally advanced head and neck cancer received Hyperfractionated radiotherapy (HFRT) with concurrent chemotherapy. Patients received 6760cGy to 7260cGy in 66-70 fractions, 110cGy per fraction, 2 fractions per day with 6 hours gap over 7-8 weeks and weekly injection cisplatin 30 mg/m2.Results: At the endpoint of 6 months which was the minimum follow up for all patients the overall response and complete response was 86.66% and 66.66% respectively. The complete response rate was 80% and 60% in Stage III and Stage IV patients respectively.Conclusion: Hyperfractionated Radiotherapy with concurrent chemotherapy gives good local control and improved overall response in locally advanced head and neck squamous cancer. However larger studies should be done to confirm the results.